Immunogenicity of COVID-19 Vaccination in People Living with HIV: Progress and Challenges - Jin-Wen Song; Lili Shen; Fu-Sheng Wang (​​​​​​​​Infectious Diseases & Immunity)
Abstract. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has resulted in numerous confirmed cases and deaths worldwide. Recent studies have shown that people living with HIV (PLWH) are prone to develop severe illness and poor outcomes if they experience coronavirus disease 2019 (COVID-19), especially those with uncontrolled viremia and low CD4 T-cell count. Therefore, many countries prioritized PLWH for COVID-19 vaccination. However, lower magnitude or faster waning humoral immune responses elicited by other vaccines have been documented in PLWH, raising concerns regarding the efficacy of the COVID-19 vaccine in these specific populations. Here, we summarize the current progress in the immunogenicity and efficacy of different types of SARS-CoV-2 vaccinations in PLWH and highlight several challenges faced by PLWH in the current COVID-19 pandemics.